Clinicopathological predictors of survival in resected primary lung adenocarcinoma. Issue 5 (7th April 2021) - Jhala, Hiral; Harling, Leanne; Rodrigo, Alberto; Nonaka, Daisuke; Mclean, Emma; Ng, Wen; Okiror, Lawrence; Bille, Andrea
Abstract : Aims: Primary lung adenocarcinoma consists of a spectrum of clinical and pathological subtypes that may impact on overall survival (OS). Our study aims to evaluate the impact of adenocarcinoma subtype and intra-alveolar spread on survival after anatomical lung resection and identify different prognostic factors based on stage and histological subtype. Methods: Newly diagnosed patients undergoing anatomical lung resections without induction therapy, for pT1-3, N0-2 lung adenocarcinoma from April 2011 to March 2013, were included. The effect of clinical–pathological factors on survival was retrospectively assessed. Results: Two hundred and sixty-two patients were enrolled. The 1-year, 3-year and 5-year OS were 88.8%, 64.3% and 51.1%, respectively. Univariate analysis showed lymphovascular, parietal pleural and chest wall invasion to confer a worse 1-year and 5-year prognosis (all p<0.0001). Solid predominant adenocarcinomas exhibited a significantly worse OS (p=0.014). Multivariate analysis did not identify solid subtype as an independent prognostic factor; however, identified stage >IIa, lymphovascular invasion (p=0.002) and intra-alveolar spread (p=0.009) as significant independent predictors of worse OS. Co-presence of intra-alveolar spread and solid predominance significantly reduced OS. Disease-free survival (DFS) was reduced with parietal pleural (p=0.0007) and chest wall invasion (p<0.0001), however, adenocarcinoma subtype had no significant impact on DFS. Conclusions: Our study demonstrates that solid predominant adenocarcinoma, intra-alveolar spread and lymphovascular invasion confer a worse prognosis and should be used as a prognostic tool to determine appropriate adjuvant treatment.